Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2016)
Table of Content Death Becomes Her: Maria Hassabi at the Museum by Claire Bishop Ed Atkins Missing Persons by Andrew Durbin I’m Not Too Sad to Tell You by Leslie Jamison Mary Shelley App by Bruce Hainley Theaster Gates Just What Is It That Makes Today’s Artist-Led Urban Development So Different, So Appealing? by Andrew Herscher Rebuilding the Future by Christine Mehring & Sean Keller Raise High the Roof Beam: Theaster Gates and Cathedrals by Dieter Roelstraete Lee Kit Scenes of Everyday Life by Doryun Chong Claiming Space: Occupation and Withdrawal in the Work of Lee Kit by Christina Li Marked by Hand by Francesca Tarocco Mika Rottenberg Rottenberg Pearls by Jonathan Beller “Eww, Gross!”: Mika Rottenberg’s Late Capitalist Feminism by Amelia Jones: Mika Rottenberg’s Bachelor(ette) Machines by Germano Celant Fuck Seth Price by Claire Lehmann
﻿Issues of materiality, embodiment, and subjectivity are explored in this volume of Parkett. Our four artist-collaborators tackle the vast questions of who we are as individuals, how we interact with others, and what we create with our labor. (editorial by publisher)
boek
Keywords: Atkins, Ed; Rottenberg, Mika; Kit, Lee; Gates, Theaster